Development economics theory, empirical research, and policy analysis - Schaffner, Julie (John Wiley & Sons, Inc., 2014)
Development Economics: Theory Empirical Research and Policy Analysis by Julie Schaffner offers a means to think about development and policy in a way that is disciplined by economic theory and informed by empirical research. The main goal of this text is to get readers to think rigorously using tools of economic analysis. This text will help to define development objectives, understand the development process, identify potential barriers to development, design candidate development interventions, and analyze the multidimensional impact of theory, empirical research and policy analysis within the study of economic development--Provided by publisher.